The Effect of Using Crosswords Puzzle Towards Students Vocabulary Mastery at SMP Al Razi Sinar Harapan - Suci Anggi Harianja, M. Khalid (CV. PUSDIKRA MITRA JAYA, 2023)
This study aims to obtain emphirical evidence regarding the effect of crosswords puzzle on students vocabulary mastery. This research was conducted on students class VII of SMP Al Razi Sinar Harapan. The method used in this research was a Quantitative with quasioner-experimental from total sample of 34 students as a sample of 112 popultions which were divided into 2 classes, 17 students for the experimental class and 17 students for control class. Before giving treatment, the researcher gave a pre-test. Then the researcher tught the experimental class with the media crosswords puzzle and in the control class without media crosswords puzzle. After two meetings, the researcher gave post-test to both class. In the analysis of pre-test and post-test assessment data using thirty-five essay questions, after that it was analyzed using the t-test formula. The results of this study indicate that media crosswords puzzle are effective in learning vocabulary mastery in class VII of SMP Al Razi Sinar Harapan. This is based on the results of the t-test which shows that t-observed > t-table (3,01 > 2,03). At 5% significance. This means that Ha is accepted and Ho is rejected. Therefore it can be concluded thata the media crosswords puzzle has an effect on students vocabulary mastery.